PROTOTIPE MESIN SANTAN KELAPA BERBASIS PLC OUTSEAL - Kurniawan, Muhammad; Hasan Hasan; Ardi Marwan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to design and realize a prototype of a coconut milk machine based on Outseal PLC that integrates the grating and squeezing processes in one automatic system. The system uses Outseal Mega V.2 PLC as the main controller with Arduino Uno support for sensor reading. A load cell sensor is used to detect the weight of 1 kg of grated coconut as a parameter for the process transfer to the squeezing stage. The test results show that 1 kg of grated coconut produces approximately ½ liter (500 ml) of coconut milk. An ultrasonic sensor is used to detect the height of the coconut milk surface in the container, which is approximately 14.8 cm at a volume of 500 ml as the system's stop limit. The process of making coconut milk using the machine takes approximately 40 minutes, faster than the manual process which takes approximately 60 minutes. The results of the study indicate that the tool is able to increase time efficiency and reduce manual work processes in making coconut milk.